Characteristics of persons with spinal cord injury who drive in Malaysia and its barriers: a cross sectional study - Lee, Richard Chee Houw; Hasnan, Nazirah; Engkasan, Julia Patrick (Springer Nature, 2018)
Study design: Cross sectional study. Objectives: To determine the prevalence, characteristics of and barriers to driving among persons with a spinal cord injury (SCI). Setting: SCI Rehabilitation Clinic, University Malaya Medical Centre (UMMC). Methods: This is a questionnaire-based study on persons with SCI who attended the UMMC SCI Rehabilitation Clinic between June 2015 and November 2016. The questionnaire comprised demographic data, clinical characteristics, driving variables, Spinal Cord Independence Measure III, WHOQOL-BREF, and Craig Handicap Assessment and Reporting Technique Short Form. Malaysians aged greater than 18 years old with any etiology and levels of SCI, had no other physical disabilities and not suffering from progressive illness were recruited. A single investigator administered the questionnaire via face-to-face interviews. Results: A total of 160 participants were included in this study. Overall, 37% of persons with SCI drove and owned a modified vehicle. Almost half of persons with paraplegia (47%) drove, but only 12% of tetraplegia did. A majority (93%) of those who drove aged below 60 years, and had higher level of independence in activity of daily living. More drivers (81%) compared to non-drivers (24%) were employed; drivers also reported better community reintegration and quality of life. Three commonest barriers to driving included medical reasons (38%), fear and lack of confidence (17%), and inability to afford vehicle modifications (13%). Conclusions: The percentage of persons with SCI driving post injury is low. Based on the findings of this study, more efforts are needed to motivate and facilitate persons with SCI to drive.